Clinical Documentation Quality and Adherence to Preventive Care Guidelines in a Student-Run Free Clinic - Rola, Ishan; Dunlop, Hayley M; Shihabuddin, Courtney; Cooper, Robert (Journal of Student-Run Clinics, 2025)
The Columbus Free Clinic (CFC) is the largest interprofessional student-run free clinic in Ohio that provides medical and social services to uninsured and underinsured individuals. In recent years, CFC’s care model has gradually shifted away from serving as an acute care resource and towards a longitudinal provider role for uninsured and underinsured residents in the greater Columbus area. Limited data on the quality of our patient charts and limited ability to utilize data to inform longitudinal programs and chronic care treatment led us to evaluate documentation quality in a sample of our patient charts with the aim of improving the quality of care in our clinic. We assessed documentation of vital signs, social history, family history, past medical history, obstetric history, and preventive screenings. We randomly selected 10% of patient charts. As of June 2023, our clinic had 4971 patient records; therefore, our sample size was 497 charts. Substantial gaps in reporting patient social history, family history, and past medical history were noted, as well as gaps in reporting patient cancer screenings. We describe our chart audit process and chart review materials here with the aim of providing other student-run free clinics with a model to assess the quality of their patient charts and improve the quality of their clinical documentation, thereby improving overall patient care. The results of this chart audit have promoted the development of new volunteer training initiatives, new volunteer recruitment and the creation of chart quality and research committees, which will allow us to improve the quality of CFC patient charts and continuity and quality of patient care.